The Analysis Static of Chassis Robot Arm as Design Modification Induction Melting Furnace Machine Using FEA Method - Eka Bima Saputra; Ahmad Zohari; Andriansyah; Wahyu Bambang Sulistyo (UIR PRESS, 2023)
Induction furnace is a metal melting furnace that uses heater. The high temperatures can cause work accidents if not carefully. The cause of work accidents, especially machines is had mistake when initially machine designed. An alternative solution is to make improvements the machine. The researcher made a robot arm design that functions to transfer melting products and reduce work accidents like being exposed to melted metal. The researcher’s purpose is to analyze the design static of robot arm as modification induction melting furnace machine. The method is to study previous research literature related to static simulation. Researchers use the SolidWork premium 2018 software which consists of stress (von mises), displacement, and FOS (factor of safety) calculations. Based on the static simulation results, it can be concluded that the highest values ​​of simulated stress (von mises) at 5N, 10N, and 15N loads were 13.926Mpa, 27.728Mpa, and 41.531Mpa which categorized as feasible because they were below yield strength value of 64.205Mpa. Simulation displacement, the design experienced the most significant deformation at 15N load with value of 0.337 mm. The FOS (factor of safety) value each loading were 4.610; 2.315; and 1.474 which fulfills the static load safety requirement 1.25.